The cost of honor - Stewart, Diana Muñoz (Stewart, Diana Muñoz. Black ops confidential., 2020)
"The only male to be adopted into the notorious Parish family, Tony Parish always did right by his vigilante sisters. But when an attempt to protect one of them went horribly wrong, he had to fake his own death to escape his fanatical family. Tony set sail and ended up in Dominica- face to face with the woman of his dreams... When Honor Silva plunged into stormy waters to rescue a drowning kiteboarder, she had no idea resuscitating the sexy stranger would bring life-changing love--and life-threatening danger--crashing into her world."--Page 4 of cover.